Flow modification around a circular cylinder applying splitter plates - Mahjoub, Babak; Ahmad, Kamarul Arifin; Wiriadidjaja, Surjatin (Universiti Putra Malaysia Press, 2016)
A number of different studies were reviewed to investigate the functionality of splitter plates for the purpose of drag reduction and vortex elimination behind a circular cylinder. The studies were carried out numerically or experimentally in different combinations of Reynolds range, 2D or 3D dimensions, with intention of drag reduction, vortex suppression or both. Results were compared to discover the generalities of a splitter plate's applications and its performance in drag reduction and vortex control. The reduction of 12% up to 38.6% in drag coefficient suggests that all reviewed studies verified the effectiveness of upstream plate in drag reduction. Varied upstream plate's gap ratios (gap between the plate and cylinder) were tested and the optimum position was obtained. For the finite cylinder case, however, the studies discovered that the effectiveness of upstream plate decreased severely and thus, are barely considered as a drag reductive tool for shorter cylinders. Although downstream plate influences drag force, its prominent application is found to be vortex shedding elimination (up to 14.7%). The length ratio and gap ratio of downstream plate were varied in these studies and it was found that the length ratio was a more important factor compared with the gap ratio in the case of vortex suppression.